What platelets tell us about CARs - Dreger, Peter (Blood, 2025)
In this issue of Blood, Rejeski et al introduce a new grading system, termed T-ICAHT, as an important tool for assessment and quantification of immune effector cell-associated hematotoxicity (ICAHT).1Chimeric antigen receptor T-cell therapy (CART) has become a cornerstone of salvage treatment of B-cell malignancies, such as B-lineage acute lymphoblastic leukemia, most B-cell lymphomas, and multiple myeloma. However, the high efficacy of CARTs comes at the price of some significant toxicities, including hematotoxicity, which is probably the most important driver of nonrelapse mortality (NRM) associated with CART use.2 The most prominent feature of CART-associated hematotoxicity is neutropenia, which can be categorized using the N-ICAHT grading system.3 The N-ICAHT score helps to standardize post-CART neutropenia management and research efforts.3 Moreover, N-ICAHT grading can predict CART outcomes, including infections, NRM, and survival.4
Gesehen am 01.12.2025